2021
DOI: 10.7554/elife.69333
|View full text |Cite
|
Sign up to set email alerts
|

The entorhinal cortex modulates trace fear memory formation and neuroplasticity in the mouse lateral amygdala via cholecystokinin

Abstract: Although fear memory formation is essential for survival and fear-related mental disorders, the neural circuitry and mechanism are incompletely understood. Here, we utilized trace fear conditioning to study the formation of trace fear memory in mice. We identified the entorhinal cortex (EC) as a critical component of sensory signaling to the amygdala. We adopted both loss-of-function and gain-of-function experiments to demonstrate that release of the cholecystokinin (CCK) from the EC is required for trace fear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 55 publications
4
24
0
Order By: Relevance
“…LFS induces long-term depression (LTD) when both the number of stimulation pulses (typically 900 pulses) and the current of stimulation are large (Collingridge, Peineau et al 2010). As previously reported, we concluded that HFS induced the release of CCK from the presynaptic terminals, leading to LTP in the neocortex and amygdala (Chen, Li et al 2019, Feng, Su et al 2021). We then hypothesize that the application of the CCKBR agonist (CCK4) induces LTP in the BLA even under the LFS paradigm.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…LFS induces long-term depression (LTD) when both the number of stimulation pulses (typically 900 pulses) and the current of stimulation are large (Collingridge, Peineau et al 2010). As previously reported, we concluded that HFS induced the release of CCK from the presynaptic terminals, leading to LTP in the neocortex and amygdala (Chen, Li et al 2019, Feng, Su et al 2021). We then hypothesize that the application of the CCKBR agonist (CCK4) induces LTP in the BLA even under the LFS paradigm.…”
Section: Resultssupporting
confidence: 76%
“…The fear memory can be inactivated and reactivated by LTD and LTP (Nabavi, Fox et al 2014). Recently, we found that activating CCK-positive projection from the EC to LA by a high-frequency laser stimulation modulated the neuronal plasticity, and potentiated auditory response in LA neurons (Feng, Su et al 2021). We implanted an optical ber in the BLA after virus injection into the EC of CCK-Cre mice (AAV-EF1a-DIO-ChETA-EYFP in the experimental group, ChETA; AAV-EF1a-DIO-EYFP in the control group, EYFP; g. 2 a b).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations